(untitled) (Journal of Oriental Studies, 2018)
The article deals with the movement of Uighurs from their historical homeland to Kazakh lands, to the Chinese empire or to the murders of the Russian Empire, violence and poetry of the great destiny of the Uighur people. The works of Uighur diaspora poets, who are living in independent Kazakhstan, are criticized for their lack of respect for historical attitudes